ANALISIS PENYESUAIAN DIRI DITINJAU DARI TIPE KEPRIBADIAN PESERTA DIDIK KELAS X SMAN 1 PONTIANAK - Damayanti, Herlina; Purwanti, Purwanti; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to obtain information about the adjustment in terms of personality type of students grade X SMAN 1 Pontianak. The method used is descriptive method, using Causal-Comparative Studies. The sample in this research is 87 students of class X IPS SMAN 1 Pontianak. Data collection techniques are indirect communication techniques and direct communication, data collection tool that is inventory and interview guide. Data analysis technique is descriptive statistical technique. The results of data analysis, indicating that the students' self-adjustment of each personality type corresponds to the characteristic personality type by Littauer. The quality of self-adjustment of Choleris personality type reached 81% with good category, Phlegmatis reached 78% good category, Sanguinis reached 75% good category, and Melancholy reached 74% good category. In this case, the counselor teacher has not been instrumental in helping learners understand personality types, but has made curative efforts in the problem of self-adjustment of learners. Keywords : Adjustment, Personality Types, Florence Littauer